2006
DOI: 10.1128/jcm.00316-06
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Infections Due to Multidrug-Resistant Bacteroides fragilis Group Strains

Abstract: Bacteroides fragilis group strains are still considered susceptible to most antimicrobial agents used for the treatment of infections caused by anaerobic organisms. We describe two cases of infections due to isolates simultaneously resistant to clindamycin, tetracycline, cefoxitin, piperacillin-tazobactam, and imipenem and, in one of the two cases, to metronidazole. Such infections, although still rare, do exist and tend to complicate treatment. First case report.A 71-year-old man was admitted to the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…In the study of Katsandri et al (2006), it was shown in the first case described that the strain was metronidazolesusceptible but imipenem-resistant, and the authors detected a cfiA gene, which is associated with carbapenem resistance. There was no further description and no information about IS elements.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Katsandri et al (2006), it was shown in the first case described that the strain was metronidazolesusceptible but imipenem-resistant, and the authors detected a cfiA gene, which is associated with carbapenem resistance. There was no further description and no information about IS elements.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, resistance to metronidazole among B. fragilis group isolates has been observed worldwide (33,135). Resistant B. fragilis group isolates carry one of nine known nim genes (nimA-I) on either the chromosome or a mobilizable plasmid that seems to encode a nitroimidazole reductase, which converts 4-or 5-Ni to 4-or 5-aminoimidazole, preventing the formation of toxic nitroso residues necessary for the agent's activity.…”
Section: Metronidazole and Tinidazolementioning
confidence: 99%
“…Additionally there are clear differences in the resistance according to the geographical areas [1] and even differences can be found in resistance patterns in different hospitals in a single city, which may be due to the variability in selecting antibiotics for empirical treatment [2]. Several papers reported about cases caused by broadly multidrug-resistant B. fragilis isolates [6,7,16,17], as well as number of reports describes the development of resistance in vitro or in vivo in the presence of antibiotics [18,19]. These events emphasize the need for antimicrobial susceptibility testing of anaerobes not only during periodical surveillances in different geographical areas, but also during the everyday routine laboratory testing.…”
Section: Discussionmentioning
confidence: 98%